UJI EFEKTIVITAS AIR PERASAN DAUN JERUK NIPIS (Citrus aurantifolia Swingle.) SEBAGAI PESTISIDA NABATI TERHADAP LALAT BUAH TAHUN 2020 - hengki frengki manullang (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Fruit fly is one of the potential pests of fruit destroyers which is very loss to fruit farmers. Lime leaves (Citrus aurantifolia Swingle.) Have been examined to contain several compounds that have the potential to control fruit fly pests. The purposes to find out whether the juice of lime leaves is effective as a vegetable pesticide against fruit flies. In this study using experimental methods. With the stages of sampling, sample processing, phytochemical screening, making juice, making fruit fly traps, and testing the juice of lime leaves as vegetable pesticides with different concentrations of 0%, 5%, 10%, 15% and 20% sprayed on the surface of guava fruit (Psidium guajava) and observed its effect on fruit flies. The average results of research on the juice of lime leaves as a vegetable pesticide against fruit flies indicate that the higher the concentration the higher the number of fruit fly deaths based on observations made for 3 days. Based on data analyzed statistically by the ONE WAY ANOVA method. It can be concluded that at a concentration of 20% the juice of lime leaves is the most effective as a vegetable pesticide. Based on the results of this study, the juice of lime leaves is expected to be an alternative as a vegetable pesticide.